Taking time to think: The tyranny of being “too busy” and the practice of wildlife management - Decker, Daniel J.; Pomeranz, Emily F.; Forstchen, Ann B.; Riley, Shawn J.; Lederle, Patrick E.; Schiavone, Michael V.; Baumer, Meghan S.; Smith, Christian A.; Frohlich, R. Kipp; Benedict, R. Joseph; King, Richard (Frontiers in Conservation Science, 2022)
Wildlife professionals in the United States are in a paradoxical situation, often expressed in statements such as: “My professional responsibilities make it impossible to find time to be as thoughtful about my work as I would like.” Many wildlife professionals who find themselves in this situation figuratively throw up their hands when presented with an opportunity to consider novel ideas or explore new possibilities and declare: “I’m too busy; I have more to do than ever before with no time left over to think about new ideas and approaches let alone create them.” If the wildlife profession addresses this conundrum openly and mitigates the detrimental consequences it has on individuals and their effectiveness, we suggest enhanced conservation will occur. Toward this end, we explore three questions: (a) what is preventing wildlife professionals from setting a greater priority on taking time to reflect critically about their work? (b) what are the perceived consequences of the current condition? and (c) what are people doing to reduce the problem? The root of the issue is manifold, from the fallacy of equating activity to productivity, the normalization of “busyness”, and a tendency towards action bias, to additional institutional challenges at the organizational level. Efforts to improve the situation will be a substantial undertaking, likely requiring simultaneous interventions at multiple levels guide individual and organizational prioritization processes, implemented over time, and continuously renewed. This article describes the tyranny of being too busy—its symptoms, causes, and effects—and presents ideas for mitigating the problem offered by wildlife professionals and the organizational behavior literature.